PERBEDAAN PEMAHAMAN KONSEP MATEMATIKA MENGGUNAKAN METODE TAI DAN PAIR CHECKS DITINJAU DARI MINAT BELAJAR - Limoi Ani; Rahmat Winata; Rizki Nurhana Friantini (Jurnal Karya Pendidikan Matematika, 2019)
This research is quantitative research. The research was conducted on November 5-24, 2018. The population in this study were class X students of SMA Negeri 1 Jelimpo in the 2018/2019 school year of Landak Regency, which consisted of class X MIA, X IIS A and X IIS B totaling 109 students. The sampling technique is Cluster Random Sampling. Data collection methods used tests, questionnaires, and documentation. Data analysis techniques with prerequisite test consisting of balance test, normality test and homogeneity test, followed by a hypothesis test consisting of two-way unequal cell anava test and further test. Based on the calculation results obtained: (1) the TAI method is better than the Pair Checks method of understanding concepts, (2) high learning interest has better understanding of concepts than moderate and low learning interest, and moderate learning interest is better than low interest in learning, ( 3) In each learning method high learning interest has better understanding of concepts than moderate and low learning interest, and moderate learning interest is better than low interest in learning, (4) At each level of learning interest students have high and moderate learning interest in the TAI method and the Pair Checks method has the same good concept, so for students who have a low interest in learning with the TAI method they have a better understanding of the concepts than students with the Pair Checks method.